Global burden, temporal trends and geographic disparities of younger-onset atrial fibrillation in adults aged 30–45 years, 1990–2021: a population-based study - Sun, Jiayi; Dong, Jiayang; Liang, Lifeng; Xue, Zuochen; Ding, Jun (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThis study aimed to estimate the global burden, temporal trends, and geographic disparities of younger-onset atrial fibrillation (AF) in adults aged 30–45 years across 204 countries from 1990 to 2021, using data from the Global Burden of Disease Study. Focusing on this under-researched age group, we aimed to characterize the epidemiology of premature AF and its implications for prevention strategies.MethodsWe analyzed the global burden of younger-onset AF (30–45 years) from 204 countries using Global Burden of Disease Study 2021 data. The primary outcomes included age-standardized prevalence, mortality, disability-adjusted life years (DALYs), and average annual percentage change (AAPC).ResultsFrom 1990 to 2021, the age-standardized prevalence of AF among young and middle-aged adults decreased slightly from 57.81 to 57.48 cases per 100,000 population, with an AAPC of 0 (95% CI −0.05 to 0.05). Age-standardized mortality rates (ASMR) increased from 0.04 to 0.05 per 100,000 population, with an AAPC of 0.17% (95% CI 0.08 to 0.26). The age-standardized DALYs rate (ASDR) rate rose from 6.98 to 7.08 per 100,000 population (AAPC 0.05%, 95% CI −0.02 to 0.11). Men exhibited higher AF-related mortality, with an AAPC of 0.3% (95% CI 0.14 to 0.47). Higher Socio-demographic Index (SDI) countries showed higher AF prevalence (e.g., 111.54 per 100,000 in Australasia) but lower mortality rates, whereas low-SDI countries had higher mortality rates (AAPC 0.49% for low-middle SDI). Regional analysis revealed the highest prevalence increase in East Asia (AAPC 0.72%).ConclusionsFrom 1990 to 2021, the global age-standardized prevalence and ASDR for AF in adults aged 30–45 remained stable, though ASMR slightly increased, particularly among men and in regions with lower SDI. These findings emphasize the need for targeted prevention strategies to reduce AF-related mortality in this population.